Wind propulsion options for energy ships - Clodic, Gaël; Gilloteaux, Jean-Christophe; Babarit, Aurélien (ASME 2018 1st International Offshore Wind Technical Conference, 2018)
ASME 2018 1st International Offshore Wind Technical ConferenceASME 2018 1st International Offshore Wind Technical ConferenceSan Francisco, California, USA, November 4–7, 2018Conference Sponsors: Ocean, Offshore and Arctic Engineering DivisionISBN: 978-0-7918-5197-5 International audience A new concept has emerged for far offshore wind energy conversion. It is the wind energy ship (1). It consists of a ship propelled by wind sails towing a water turbine. The water turbine produces electricity. The electricity is converted into a fuel (hydrogen for example). When the tanks are full, the ship sails to a terminal where the fuel is unloaded. Then, it can start a new charging cycle.An energy ship consists in several sub-systems: wind propulsion subsystem, hull, water turbine, energy storage. The focus of this paper is on the wind propulsion subsystem because of the many options available. Indeed, it has been proposed to implement rigid sails (2, 3), kite wings (4, 5), airfoils (1, 7) or Flettner rotors (6).Applying systems engineering, key requirements for the wind propulsion have been identified for the energy ship application. They are presented in the paper. Next, the advantages and drawbacks of each technology are discussed and most promising options are highlighted.